An Empirical Analysis of Money Supply Process in Nepal - Shrestha, Prakash Kumar (NRB Economic Review, 2013)
This paper examines the money supply process in Nepal empirically on the basis of mainstream and Post-Keynesian theoretical perspectives for both pre and post-liberalization period covering the sample period of 1965/66-2009/10. The relative contribution of different components of money supply has been computed and the money supply as well as money multiplier function has been estimated. Empirical results show that disposable high powered money is found to be a major contributor to the change in monetary aggregates without any significant structural break. However, the degree of controllability of high powered money is not strong, and neither CRR nor Bank Rate has been effective monetary policy tools so far. Open market operation is found statistically significant only at 10 percent level of significance to influence disposable high powered money. On the other hand, money multipliers are affected by currency ratio, time deposits ratio and excess reserve ratio, but not by CRR. On the other hand, Granger causality based test of Post-Keynesian hypothesis reveals that money supply endogeniety cannot be ruled out. Hence, monetary policy framework needs to be changed accordingly and OMO should be strengthened further.